Falls of the Ohio River : Archaeology of Native American Settlement - Carlson, Justin N.; Bader, Anne Tobbe; Pollack, David, 1951- (Book collections on Project MUSE., 2021)
"Falls of the Ohio River presents current archaeological research on an important landscape feature of what is now Louisville, Kentucky, demonstrating how humans and the environment mutually affected each other in the area for the past 12,000 years"--